PENGEMBANGAN E-BIG BOOK DALAM PEMBELAJARAN MEMBACA PEMAHAMAN MENGGUNAKAN MODELTHINK PAIR SHARE (TPS) DI KELAS IV SEKOLAH DASAR - Meldini, Taura; Muhammadi; Chandra; M. Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The restricted utilization of technology-based teaching resources in fourth-grade elementary school reading comprehension instruction is the driving force behind this study. Pupils are less engaged in the learning process and struggle to comprehend the reading material. This research aims to develop an E-Big Book as teaching material for reading comprehension using the Think Pair Share (TPS) model. The ADDIE development paradigm, which consists of Analysis, Design, Development, Implementation, and Evaluation, was utilized in the research and development (R&D) process. Expert validators, teachers, and sixty fourth-graders from SDN 17 Gunung Pangilun, SDN 03 Alai Timur, and SD Negeri 21 Parak Kopi served as the subjects. The results showed that the E-Big Book obtained a validity percentage of 96.6%, categorized as very valid. The practicality results were 95%, 97.5%, and 92.5%, while the N-Gain scores were 0.72, 0.77, and 0.77, categorized as high. Thus, the E-Big The book is reliable, useful, and efficient for reading comprehension learning using the Think Pair Share (TPS) model.